A Grid-Tie Micro-inverter Software Development Based on a Low Cost Multiprocessor Platform - Götz, Marcelo; Gobetti, Marcelo Wagner; Líbano, Fausto Bastos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
The software development of a three-phase micro-inverter on a low cost Multiprocessor platform, available on the BeagleBone Black, is presented. Apart from signal conditioning circuits, it is aimed solely the use of existing components in the board. Real-time systems are used for a strict time control over the three-phase sinusoidal modulation and over the sampling used for the internal control system. The remote user interface running under a web server is set up, having access to memory registers and being able to run scripts on the system. Valid Brazilian norms are analyzed, from which inverter requirements are extracted. It is demonstrated to be viable the use of the BeagleBone Black for the proposed project in terms of functionality.